Sex‐specific composite scales for longitudinal studies of incipient Alzheimer's disease. Issue 1 (1st January 2019) - Banks, Sarah J.; Shifflett, Benjamin; Berg, Jody‐Lynn; Sundermann, Erin; Peavy, Guerry; Bondi, Mark W.; Edland, Steven D.
Abstract: Introduction: The impact of Alzheimer's disease (AD) on cognitive decline differs by sex. Composite scores are useful as singular outcomes in clinical trials, yet to date these have not been developed to measure sex‐specific change. Method: We derived optimal composites from component scales available in the AD Neuroimaging Initiative (ADNI) database among cognitively normal and mild cognitively impaired subjects who are cerebrospinal fluid amyloid‐β positive for early AD. Maximally sensitive composites were constructed separately for men and women using standard formulas. We compared the statistical power of the composites with the ADNI Prodromal Alzheimer's Cognitive Composite. Results: Among 9 cognitive measures and clinical dementia rating sum of boxes, the optimal sex‐specific composites included 5 measures, including the clinical dementia rating and 4 distinct cognitive measures. The sex‐specific composites consistently outperformed sex‐agnostic composites and the ADNI Prodromal Alzheimer's Cognitive Composite. Discussion: Sex‐specific composite scales may improve the power of longitudinal studies of early AD and clinical trials.